دراسة تقويمية لمادة جغرافية الصناعة من وجهة نظر طلبة المرحلة الثالثة (Journal of the College of Basic Education, 2026)
The study aimed to identify the most important strengths and weaknesses available in the Industrial Geography subject from the point of view of third-year students in the Geography Department. The study is limited to third-year students in the Geography Department / College of Education / Al-Mustansiriya University. The cognitive boundaries were represented by the Industrial Geography subject, while the temporal boundaries were represented by the Industrial Geography subject calendar for the academic year 2023-2024 AD. The sample size was (194) male and female students for both morning and evening studies. The researchers relied on the questionnaire form as a tool for the current study, which was represented by (6) fields, each field has (5) paragraphs. After processing the data statistically using the Statistical Package for Social Sciences (SPSS), the results of the study showed that there is a difference in the responses in terms of there being paragraphs that were achieved according to the criterion followed by the researchers in their current study, and there are paragraphs that were not achieved as shown in Tables (1 to 6). These were the results that the researchers found by using the weighted mean and the percentage weight as a statistical means of During the students' responses to the questionnaire directed to them, and through the results of the study, the researchers concluded in general that third-year students confirm that the vocabulary of the industrial geography subject included in this subject is diverse in its topics and content, and the interest of the majority of the subject's teachers in the theoretical aspect and the neglect of the practical (applied) aspect to some extent. From the results and conclusions of the study, the researchers recommended several recommendations, including the necessity of informing the industrial geography subject's teachers of the objectives of the subject and following up on it every academic year and working to provide books and sources related to it according to its modernity and developing it in libraries and distributing it to college students whenever there is any newness in it. After completing this study and completing the current study, the researchers suggest conducting future studies by master's and doctoral students and researchers in general to conduct an evaluation study on other subjects other than the current subject.